2015
DOI: 10.5414/cn108541
|View full text |Cite
|
Sign up to set email alerts
|

Tubular dysfunction in renal transplant patients using sirolimus or tacrolimus

Abstract: Distal RTA and urine concentrating defect were highly prevalent after kidney transplantation both in the sirolimus and tacrolimus treated patients. Acidification test was essential for the appropriate diagnosis of dRTA while dipstick urine specific gravity test was able to detect urine concentrating defect in this population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
8
0
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 15 publications
1
8
0
1
Order By: Relevance
“…Rapa is regularly used as an immunosuppressant in solid organ transplantation rejection, and its use has also been recently exploited for certain autoimmune diseases and cancers. 33 35 However, Rapa's systemic use has been limited by its side effects, including stomatitis, 36 nephrotoxicity, 37 , 38 and pulmonary toxicity. 39 In our previous study, nephrotoxicity was observed even with short-term use (three doses over 1 week).…”
mentioning
confidence: 99%
“…Rapa is regularly used as an immunosuppressant in solid organ transplantation rejection, and its use has also been recently exploited for certain autoimmune diseases and cancers. 33 35 However, Rapa's systemic use has been limited by its side effects, including stomatitis, 36 nephrotoxicity, 37 , 38 and pulmonary toxicity. 39 In our previous study, nephrotoxicity was observed even with short-term use (three doses over 1 week).…”
mentioning
confidence: 99%
“…A high prevalence of distal RTA has been documented in the transplant recipients receiving the mTOR inhibitor sirolimus, suggesting that this immunosuppressant may also cause distal tubular dysfunction. However, it is known if sirolimus can cause proteinuria and hypokalemia, the mechanism of development and prevalence of RTA in these patients remain unclear (3,34).…”
Section: •Other Causesmentioning
confidence: 99%
“…The amount of alkali administered should compensate for the urinary loss of bicarbonate plus the amount of acid generated by the protein catabolism. Besides, it has been strongly proposed that alkalitherapy represents a welltolerated, safe and cost-effective treatment which can slow the progression towards graft failure, therefore prolonging long-term graft survival (34). In clinical practice, metabolic acidosis is usually corrected when serum bicarbonate level is <22 mmol/L (3).…”
Section: Rta Treatmentmentioning
confidence: 99%
“…Despite its high clinical efficiency, tacrolimus has been well known for its adverse reactions. In particular, patients receiving tacrolimus chronically are at high risk to develop cholestasis and renal damage (Yadav et al, 2013;Banhara et al, 2015). Nephrotoxicity was reported in approximately 52% of kidney transplantation patients, 40% of liver transplantation patients receiving tacrolimus and in 59% of heart transplantation patients in US randomized trial (Boudjema et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…In concordance, the results obtained from the present study showed that microscopical examination of the kidney of adult albino rats treated with tacrolimus showed vacuolation of glomeruli and distal tubule. Banhara et al (2015) reported that distal tubular dysfunction is prevalent among kidney transplant patients using tacrolimus. Moreover, Boudjema et al (2011) suggested that tacrolimus induced nephrotoxicity is dose-dependent in transplant patients.…”
mentioning
confidence: 99%